Shared Language Erosion: Rethinking Immigrant Family Communication and Impacts on Youth Development - Ronald B. Cox; Darcey K. deSouza; Juan Bao; Hua Lin; Sumeyra Sahbaz; Kimberly A. Greder; Robert E. Larzelere; Isaac J. Washburn; Maritza Leon-Cartagena; Alma Arredondo-Lopez (MDPI AG, 2021)
In this paper we make the case for Shared Language Erosion as a potential explanation for the negative outcomes described in the immigrant paradox for second- and third- generation immigrants (e.g., declines in physical, mental, and behavioral health). While not negating the important role of cultural adaptation, we posit that parent-child communication difficulties due to a process we are calling Shared Language Erosion is driving the observed affects previously attributed to changes in cultural values and beliefs. Shared Language Erosion is the process during which adolescents improve their English skills while simultaneously losing or failing to develop their heritage language; at the same time their parents acquire English at a much slower rate. This lack of a common shared language makes it difficult for parents and their adolescent children to effectively communicate with each other, and leads to increased parent-child conflict, reduced parental competence, aggravated preexisting flaws in parent-child attachment, and increased adolescent vulnerability to deviant peer influences.